Intellectual immunity in architecture - Ibrahim Jawad Kadhim; Rasha Noori Ahmed (Iraqi Journal of Architecture and Planning, 2017)
Architectural thought is defined as a final result of all principles and cognitive visions, which stored in human mind as a mental image, and reconfigured it to be fitting with all changes happened, that exposure the thought to all cognitive impurities (intellectual viruses), which may have a weakness and vulnerability. So immunity of thought protected it from such these impurities, when the research aims to enhance the immunity concept, and its levels of intellectual architectural process, while The research problem represented with a cognitive ambiguity of the immunity concept in the intellectual architectural process, that make the research follow an analytical method in two steps :theoretical one, is to define the concept of immunity, and the role of immunity levels in promote architectural output immunity. The research assumed is the immunity of designing productions increased when, the intellectual levels of the process (the design process) increase). Another step (practical step) is to analysis all Elective projects, leading to the immune architectural production, is a production which is compatible with the surrounding environment, whatever intellectual changes have taken place and acquired through that the continuity and longevity